Contribution of Afferent Pathways to Nerve-injury Induced Spontaneous Pain and Evoked Hypersensitivity - King, Tamara (2011)
A predominant complaint in patients with neuropathic pain is spontaneous pain, often described as “burning”. Recent studies have demonstrated that negative reinforcement can be used to unmask spontaneous neuropathic pain allowing for mechanistic investigations. Here, ascending pathways that might contribute to evoked and spontaneous components of experimental neuropathic pain model were explored. Desensitization of TRPV1 positive fibers with systemic resiniferatoxin (RTX) abolished spinal nerve ligation (SNL) injury-induced thermal hypersensitivity and spontaneous pain, but had no effect on tactile hypersensitivity. Ablation of spinal NK-1 receptor expressing neurons blocked SNL-induced thermal and tactile hypersensitivity as well as spontaneous pain. Following nerve injury, upregulation of neuropeptide Y (NPY) is observed almost exclusively in large diameter fibers and inactivation of the brainstem target of these fibers in the n. gracilis prevents tactile, but not thermal, hypersensitivity. Blockade of NPY signaling within the n. gracilis failed to block SNL-induced spontaneous pain or thermal hyperalgesia while fully reversing tactile hypersensitivity. Moreover, microinjection of NPY into n. gracilis produced robust tactile hypersensitivity, but failed to induce conditioned place aversion. These data suggest that spontaneous neuropathic pain and thermal hyperalgesia are mediated by TRPV1 positive fibers and spinal NK-1 positive ascending projections. In contrast, the large diameter dorsal column projection can mediate nerve injury-induced tactile hypersensitivity, but does not contribute to spontaneous pain. As inhibition of tactile hypersensitivity can be achieved either by spinal manipulations or by inactivation of signaling within the n. gracilis, the enhanced paw withdrawal response evoked by tactile stimulation does not necessarily reflect “allodynia”.